Rancangan dan Implementasi Aplikasi Web Point of Sales pada Butik Anak “Galery Freya” - Muhammad Sony Maulana (Jurnal Khatulistiwa Informatika, 2017)
ABSTRACTThis study aimed to design and implement an application point of sales on children's boutique "Gallery Freya" in order to improve service quality in sales, monthly transaction reports, income statements and balance sheets as well as facilitate the monitoring of inventory so availability may in check without having to manually check in the closet goods. Applications designed with server and client systems using the programming language PHP and MySQL database. The result of this research is the web application point of sales order facilitates the management of goods, recaps monthly transactions and income statement and balance sheet. Keywords: web application, information systems academic, SIBAAK